On the converse Jensen inequality for strongly convex functions - Klaričić Bakula, Milica; Nikodem, Kazimierz (Journal of mathematical analysis and applications, 2016)
Counterparts of the converse Jensen inequality for strongly convex and strongly midconvex functions are presented. The Jessen inequality and converse Jessen inequality (involving linear positive normalized functionals) for strongly convex functions are also given.